Gaya Hidup Hedonis pada Remaja Masa Kini: Pengaruh Media Sosial dan Lingkungan Sosial - Nur Ainun Ghoisani Ritonga; Cantika Zahara; Afwan Syahril Manurung (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2025)
This study aims to analyze the influence of social media and social environment on the hedonistic lifestyle among contemporary adolescents. A hedonistic lifestyle, which prioritizes the pursuit of personal pleasure and material satisfaction, has become increasingly prevalent among adolescents with the rapid development of technology, especially social media. This research employs a qualitative approach using in-depth interviews and case studies involving adolescents who are active social media users in several major cities in Indonesia. The results indicate that social media plays a significant role in shaping ideal life standards that emphasize luxury, social status, and instant gratification, which influences adolescents to pursue similar lifestyles. Additionally, the social environment, particularly family and peer groups, further strengthens adolescents' desire to gain recognition and social status through a consumerist lifestyle. The study also finds that although a hedonistic lifestyle provides momentary satisfaction, its long-term effects can be detrimental both psychologically and financially, and can worsen self-image and emotional well-being among adolescents. Therefore, it is important to provide more comprehensive education to adolescents on the wise use of social media and support the development of healthier life values within family and school environments.